Enhanced spin-orbit torques in rare-earth Pt/[Co/Ni]2/Co/Tb systems - Lew, Wen Siang (2019)
We report the enhanced spin-orbit torque (SOT) effect due to the rare-earth metal Tb in a Pt/[Co/Ni]2/Co/Tb multilayer with perpendicular magnetic anisotropy (PMA). Due to the large spin-orbit coupling in Tb, the effective dampinglike efficiency, ξeffDL, is determined to be 0.55 for 9-nm Tb as compared to ξeffDL=0.18 for the reference Pt/[Co/Ni]2/Co/Ta stack. A relatively large effective spin Hall efficiency of Tb, θeffSH,Tb, is determined to be −0.480 for Tbwith a 9-nm thickness through a Hz-biased harmonic measurement. Enhanced magnetization switching efficiency is observed with increasing Tb thickness, affirming the sizable antidamping torque responsible for deterministic switching. Furthermore, due to a more substantial interfacial coupling in Co/Tb interface than in Co/Ta interface, strong angular dependence of the dampinglike and fieldlike terms is, but diminishes with increasing Tb thickness. These results affirm that Tb plays a significant role in tuning the SOT efficiency in these structures as the increased Tb concentration leads to an enhancement of the effective spin Hall angle and switching efficiency.